Perfil dos profissionais das assessorias e métodos de treinamento utilizados - Fontana, Victor Hugo Nascimento (2013)
Athletics is a sport modality divided into different types of events, and among them there are the street racing. In the last years had a great increase on the number of events and, therefore, the number of participants. This led to the development of sports consultancies, enterprises that provide guidance for the physical activity practice, with the ideal and necessary training. Because yours business purpose, a lot of the coaches are not knowers of the training methods or his proper application form. The aim of this study was analyze the knowledge level about the training methods used by coaches in the city of Curitiba. For this purpose, based on a qualitative, exploratory and descriptive study, 11 coaches (24-38 years old), all affiliated at the Running Coach Association of Curitiba, graduates in Sport for not less than one year, answered a composed questionnaire with 11 open and closed questions. It was found that although using the same resources and training methods, and applying with similar way, they use them for different purposes. At the end of the study, in particular when addressing for the beginners training, it was concluded that the knowledge level of the surveyed coaches is satisfactory.